The Future of Fossil Fuels : From Hubbert's Peak - Deffeyes, Kenneth S. (Book collections on Project MUSE., 2014)
As debates about the effects of fossil fuels on our climate and foreign policy intensify, the question of just how much longer we can depend on this finite source of energy becomes more and more pressing. This selection from Hubbert's Peak, the leading book on the limits of our oil supply, forecasts what the future will bring for fossil fuels and what the alternatives are likely to be.